Big data compression for efficient wireless transfer - Sui, Wenjun (Nanyang Technological University, 2020)
With the tremendous growth in data size, data compression is essential for efficient data storage and transmission. Data encoding able to compress the file size of data to a relatively smaller size and most of or all the contents in the file will be retrieved after decoding. The main objective of this final year project is to develop a data compression algorithm to reduce the file size by at least ten times. The developed algorithm is also tested to find out its effectiveness to compress data size without compromising the contents. In this project, delta encoding, and variable byte encoding is proposed to reduce the size of the binary data file. It has demonstrated that binary data files can be reduced from 23 MB to about 3 MB, which is close to 15% of the original data size.